Beneficial effects of the naturally occurring flavonoid silibinin on the prostate cancer microenvironment: role of monocyte chemotactic protein-1 and immune cell recruitment. (2nd April 2016) - Ting, Harold; Deep, Gagan; Kumar, Sushil; Jain, Anil K.; Agarwal, Chapla; Agarwal, Rajesh
Summary: Employing cell culture and animal models, in this study, we demonstrated that natural non-toxic agent silibinin inhibits CAF-induced growth and invasiveness in prostate cancer cells via decreasing MCP-1 release and immune cells recruitment in tumor microenvironment. Abstract: Tumor microenvironment plays an essential role in prostate carcinogenesis and offers novel opportunities to prevent and treat prostate cancer (PCA). Here, we investigated the ability of cancer-associated fibroblasts (CAFs) to promote PCA progression, and silibinin efficacy to target this response. We collected conditioned media from CAFs treated with vehicle or silibinin, and labeled as control conditioned media (CCM) or silibinin-treatment conditioned media (SBCM), respectively. Next, we characterized the effect of CCM and SBCM treatment in several PCA cell lines (RWPE-1, WPE-1 NA-22, WPE-1 NB-14 and PC3). Result showed that compared with SBCM, CCM significantly reduces E-cadherin expression and increases invasiveness and clonogenicity in PCA cells. Further molecular studies identified monocyte chemotactic protein-1 (MCP-1) as the key component of CCM that promotes PCA invasiveness, whereas silibinin treatment strongly reduced MCP-1 expression in CAFs by inhibiting the DNA-binding activity of MCP-1 transcriptional regulators—nuclear factor-kappaB and AP-1. In vivo, silibinin feeding (200mg/kg body weight) strongly reduced TRAMPC1 allografts growth (by 68%) in syngeneic C57Bl/6 mice. TRAMPC1 tumor analysis showed that silibinin reduced MCP-1 and CAFs' biomarkers (fibroblast activation protein, α-smooth muscle actin, transforming growth factor beta 2, vimentin etc.) and significantly modulated the recruitment of immune cells in the tumor microenvironment. Similar inhibitory effects of silibinin on MCP-1 and immune cells recruitment were also observed in TRAMP PCA tissues with reported silibinin efficacy. Overall, our data suggest that silibinin can target CAF-mediated invasiveness in PCA by inhibiting MCP-1 secretion. This, in turn, was associated with a reduction in immune cell recruitment in vivo along with a marked reduction in tumor growth.